2022
DOI: 10.3390/jcm11154319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elevated Progesterone Levels on the Day of hCG on the Quality of Oocyte and Embryo

Abstract: This study is designed to investigate the effects of increased progesterone (P4) levels on the quality of retrieved oocytes and embryos during IVF. This retrospective analysis included 982 all-freezing in vitro fertilization (IVF) cycles (conducted between November 2019 and June 2020 at CHA Fertility Center Bundang, South Korea) in which serum P4 levels were measured on the day of human chorionic gonadotropin (hCG) administration. Our study revealed that the serum P4 levels on the day of hCG administration are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…However, a retrospective analysis by Woo et al (24) indicated found the maturity rates of oocytes were significantly higher in patients with high blood P4 levels, and that the maturation rates were inversely correlated with hcg-P4 levels. The study, which used 982 completely frozen IVF procedures (IVF) cycles employing GnRh antagonist down regulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, a retrospective analysis by Woo et al (24) indicated found the maturity rates of oocytes were significantly higher in patients with high blood P4 levels, and that the maturation rates were inversely correlated with hcg-P4 levels. The study, which used 982 completely frozen IVF procedures (IVF) cycles employing GnRh antagonist down regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Ten studies have been published evaluating the impact of PPE on oocyte and embryo quality since the systematic review of Venetis et al . [ 6 42 43 44 47 53 54 55 56 57 ] [ Table 2 ]. They are all retrospective cohort studies using a P threshold of 1.5–2.0 ng/ml.…”
Section: E Levated P Rogesterone and ...mentioning
confidence: 99%
“…Four studies found PPE to be associated with a lower number of top-quality blastocysts. [ 6 53 55 56 ] They proposed that delaying the trigger with an intention to retrieve greater oocyte numbers may cause elevated P and a lower number of utilisable blastocysts; which in turn would reduce CLBR. However, the remaining six studies indicated a similar number of top-quality embryos in both groups with no obvious detrimental effect of PPE on oocyte and embryo quality.…”
Section: E Levated P Rogesterone and ...mentioning
confidence: 99%